Facial Morphometrics, Voters’ Facial Preferences, and Electoral Outcomes - JAMAIRAH A NAGAMORA; ELIKA ER C BIENES; MARILOU F. SITON NANAMAN (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2016)
Elections operate in such manner that voters must have researched well the political backgrounds and platforms of the candidates they are voting. However, in absence of other information, voters tend to resort to cues such as their perception on facial appearances. This study is a pioneering study to adopt facial morphometric in testing the influence of candidates‘facial appearance on their electoral outcomes while omitting other variables such as incumbency, partisanship, and popularity. It also investigates the facial preferences of voters with low political knowledge. This study is divided two-fold. The first phase is a facial morphometric analysis of 33 senatorial candidates from the 2013 Philippine national elections. Adopting the geometric morphometric method from naturalsciences, the facial characteristics of the generated consensus image of the senatorial candidates were analyzed and identified. The second phase was conducted to verify the findings of the first phase of the study through survey questionnaires with sets of morphed faces of presumptive candidates. The researchers morphed faces from masculinity-femininity continuum and asked the facial preferences of chosen respondents. The result of the first phase was found to corroborate with the second phase. It showed that the consensus image of the 33 senatorial candidates is characterized by a hyper masculine and hyper feminine facial morphometry.